Catalyst adhesion enhancement by porous TiO2 layer formed on anodized titanium honeycomb substrate. Issue 5 (1st March 2021) - Choi, Joon-Hwan; Hwang, Jiseop; Kim, Giyeong; Choi, Jong-Jin; Ahn, Cheol-Woo; Kim, Jong-Woo; Hahn, Byung-Dong; Yoon, Woon-Ha; Min, Yuho
Abstract: Titanium honeycomb substrates having TiO2 surface with nano- to micro-sized pores were prepared by electrochemical anodization and used to make Pt-based oxidation catalyst monoliths without conventional oxide-based washcoat layers for pre-turbocharger catalyst (PTC) applications exposed to harsh conditions under very high flow rates of exhaust gas and engine vibration. Adhesion strength and CO/C3 H6 oxidation performance of the catalysts were compared with conventional washcoated FeCrAl monolith catalysts. The intermediate porous TiO2 layer formation by the anodization can dramatically enhance the catalyst adhesion strength without sacrificing the catalytic performance under GHSV (gas hourly space velocity) higher than 100, 000 h −1 for PTC.